Theoretical design of a triple-band perfect metamaterial absorber in the THz frequency range - Chunlian Cen; Zao Yi; Guangfu Zhang; Yubin Zhang; Cuiping Liang; Xifang Chen; Yongjian Tang; Xin Ye; Yougen Yi; Junqiao Wang; Jiangjin Hua (Results in Physics, 2019)
A triple-band perfect metamaterial absorber based on periodically arranged graphene split ring resonator (SRR) is proposed in this study. The calculation results by the FDTD method indicate that the SRR structure has three absorption peaks at frequencies 3.56 THz, 10.38 THz and 12.96 THz with absorption efficiency 99.57%, 99.98%, and 99.76%, respectively. By changing the chemical potential or relaxation time, the absorption characteristics of the split ring resonator structure can be flexibly tuned. Furthermore, we also examine the sensing performance of the proposed metamaterial absorber, the sensing performance of the high-frequency band is significantly higher than the low-frequency band. We believe that our results will pave the ways for the development of applications using metamaterials with high efficiency and multi-band spectral selectivity in biochemical sensing, optical switching, and modulating. Keywords: Perfect metamaterial absorber, Triple-band, Grapheme, THz, FDTD method